The importance of hard project management and team motivation for construction project performance. Issue 2 (16th April 2018) - Larsson, Johan; Eriksson, Per Erik; Pesämaa, Ossi
Abstract : Purpose: Hard project management practices, based on strict planning and control, are traditionally applied in construction projects, although research frequently promotes the importance of teams for various project outcomes. Thus, the purpose of this paper is to examine the importance of hard project management and team motivation for process performance in construction projects. A hypothesis tested is that hard project management can impair process performance if team motivation is not promoted. Design/methodology/approach: The paper presents and empirically tests a structural equation model, with and without a mediating link between hard project management and process performance, based on data from a survey of 2, 175 respondents, representing contractors and clients involved in 109 Swedish construction projects. Findings: The results confirm that hard project management is best conveyed through teams to enhance process performance. "Path analysis, " using the model with the mediating link, confirms that neglecting team motivation can significantly impair process performance. Research limitations/implications: The data set provides unusually high representation of views of contractors and clients involved in diverse Swedish construction projects. Thus, the results have likely relevance in other project-based industries and/or national settings, but this possibility requires further investigation. Originality/value: The findings show that team motivation is a key process performance factor; hard project management may indeed be important, but its effects will be enhanced by (and partially mediated through) team motivation. Thus, the findings have important theoretical and practical implications for the development of project management practices.